Pseudorabies Virus Infection in Wild Boars in Japan - MAHMOUD, Hassan Y. A.; SUZUKI, Kazuo; TSUJI, Tomoka; YOKOYAMA, Mayumi; SHIMOJIMA, Masayuki; MAEDA, Ken (Journal of Veterinary Medical Science, 2011)
In Japan, most pig populations are now free from pseudorabies virus (PRV) due to the recent success of an extensive eradication program. However, PRV infection persists in Japanese wild boars (Sus scrofa leucomystax), representing another potential reservoir for the virus in Japan. In this study, the seroprevalence of PRV in wild boars captured in three different prefectures was ascertained. A virus neutralization (VN) test showed that 6 of 173 serum samples (3%) were positive for VN antibody; glycoprotein E-ELISA revealed infection with the wild-type, but not the available vaccine strain, PRV. These results indicate that PRV has continued to spread among wild boars in Japan.